Distortion Convergence: Towards Humanist Communication for PMD/People with Mental Disorders in an Inclusive Society - Fandy Prasetya Kusuma; Subyantoro Subyantoro; Hari Bakti Mardikantoro; Rahayu Pristiwati (Universitas Negeri Semarang, 2023)
This qualitative study aims to reveal the language dynamics of PMD (People with Mental Disorders), discover odd linguistic patterns, and introduce humanist designed instruments for developing PMD’s communication skills in the landscape of Inclusive Society 5.0. The ethnographic approach focused on 12 PMDs who had psychotic disorders, bipolar disorder, post-traumatic stress disorder, and personality disorders. Distortion on recognition of communication components, repetitive production of Out of Context Speech, the offensive-aggressive Speech, and activation of emotional extralinguistic features are the major findings in this research. The curative system called “TCA : The Communication Arrow” is a prototype that was introduced as an assitive instrument for PMD to engage in inclusive society.